The use of rumen-protected amino acids and fibrous by-products can increase the sustainability of milk production - Cavallini, Damiano; Lamanna, Martina; Colleluori, Riccardo; Silvestrelli, Simone; Ghiaccio, Francesca; Buonaiuto, Giovanni; Formigoni, Andrea (Frontiers in Veterinary Science, 2025)
Optimizing the balance between dietary proteins and energy in dairy cow feeding is key to improving milk production efficiency and sustainability, with current strategies focusing on the inclusion of fibrous by-products as alternatives to cereals and the reduction of protein content through the use of rumen-protected amino acids (AA), thereby reducing competition with human food resources. This study involved 8 multiparous Holstein cows assigned to one of four isoenergetic diets: High Protein and High Cereals (HP-HC, 15% CP; 27% starch), High Protein and High Fibrous By-products (HP-HF, 15% CP; 20% starch), Rumen-Protected Amino Acids and High Cereals (AA-HC, 12% CP; 26% starch), and Rumen-Protected Amino Acids and High Fibrous By-products (AA-HF, 12% CP; 20% starch). The trial used a Latin square design, with data collected on intakes, milk production, rumen fermentation, nitrogen (N) utilization, diet digestibility and feaces residual nutrients analysis. The results showed that the ration based on fibrous by-products did not affect DMI and rumination time. Cows fed with lower protein sources and AA had significant lower ruminal ammonia levels (−1.61 mg/dL), improved N utilization efficiency (+5.61%) and reduced water intake (−21 L/day). These findings suggest that formulating rations substituting cereals with fibrous by products and reducing the N intake using rumen protected AA improve N efficiency and reduce the water consumption enhancing the environmental sustainability of milk production. Milk production and fiber digestibility were greatest in HP-HC diet indicating that some refinements of this ration strategy are needed to maintain animal performances.